Educational Tourism Based on Tri Hita Karana in Mengesta in Bali - Ni Nyoman Parwati; Trianasari Trianasari (Bina Nusantara University, 2016)
The purposes of this research are to validate the potential of superior natural resources and human resources in the tourism development of education based on Tri Hita Karana (THK) in Mengesta in Bali, to establish the centers of educational tourism, to form groups of community that supports the educational tourism based on THK, and to design media promotion. The method designed to achieve the targets are analysis, design, evaluation, and revision. Data were collected through observation, questionnaires, and interviews and analyzed using SWOT analysis and descriptive analysis. The results of this research show that there are seven learning resources that have been successfully validated, namely: dance and percussion forum, natural agricultural laboratory, Bali traditional house, agriculture training center, tracking, natural panorama and hot water bathing place, and culinary tour. The understanding and commitment of the people about educational tourism based on THK fall into good categories. Moreover, the media promotion has been successfully designed, which are in the form of art forum brochure, village tourism brochure, and a draft of guide book to educational tourism based on THK.